Extraction and Purification of β-Conglycinin and Preparation of Polyclonal Antibodies - QIAN Zhouze, LI Yan, XIA Linzhi, LIANG Ziyi, AN Xiaomin, GUO Yunxia, HAO Qinghong (Shipin Kexue, 2025)
In this study, β-conglycinin (β-CG) was extracted and purified through alkali extraction and acid precipitation combined with tangential flow filtration (TFF), and rabbit anti-β-CG polyclonal antibodies were prepared. The antibody titer and specificity were detected by indirect enzyme-linked immunosorbent assay (ELISA) and western blot (WB), respectively. Checkerboard titration was used to determine optimal antigen coating concentration and antibody dilution. Results showed that the purified product consisted of 96.70% β-CG (α’, α, and β subunits) and 3.30% acidic subunits without 2S albumin or trypsin inhibitors. The prepared rabbit anti-β-CG polyclonal antibodies effectively bound to the purified β-CG with good specificity. The optimal antigen coating concentration and antibody dilution were determined to be 1 μg/mL and 1:9 000 (V/V), respectively. This study not only provides new insights for β-CG extraction and purification, but also lays a foundation for understanding the mechanism of action of hypoallergenic β-CG and developing hypoallergenic soybean protein products.